Comparação das demandas físicas em jovens atletas de diferentes categorias e estatutos posicionais durante pequenos jogos do futebol - Júlio César Lemes (2019)
In soccer small-sided games (SSG) literature, lacks are found in physical demands imposed to athletes of different positional status or age categories, especially considering the individual speed zones distances covered and accelerations in movement axis. In this sense, this study aimed to compare the physical demands imposed by SSG in athletes of different youth categories and positional status. The present study recruited 54 athletes from a national-level soccer club of three positional status (defenders, midfielders and forwards) and three youth categories (U13, U14 and U17). The SSG teams were composed in relation to results of FUT-SAT (Tactical Evaluation System of Soccer). For data collection, GPS with accelerometers were used. For data analyse, total distance covered, distance covered in individual speed zones and accelerations in movement axis and the resultant acceleration were considered. An ANOVA two-way model, a Bonferroni’s post hoc and effect size were used to verify possible significant differences. U13 soccer athletes covered the lowest total distance. U17 soccer athletes presented higher positive accelerations on anteroposterior axis and higher negative accelerations on vertical axis compared to U13 athletes. Distances covered in individual speed zones were not different between positional status and youth categories different athletes. Thus, SSG with same configuration could generate distinct physical demands when applied in different youth categories. On the other hand, athletes of different positional status apparently do not show differences in physical demands. In conclusion, the use of individual speed zones for intensity distribution possibly to analyse different subjects like soccer athletes of different youth categories.